2017
DOI: 10.1371/journal.pone.0181745
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the production of L-glutaminase, an anticancer enzyme, from Aeromonas veronii by adaptive and induced mutation techniques

Abstract: Microbial anti-cancer enzymes have been proven to be effective and economical agents for cancer treatment. Aeromonas veronii has been identified as a microorganism with the potential to produce L-glutaminase, an anticancer agent effective against acute lymphocytic leukaemia. In this study, a selective medium of Aeromonas veronii was used to culture the microorganism. Strain improvement was done by adaptive and induced mutational techniques. A selective minimal agar media was incorporated for the growth of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
(17 reference statements)
1
13
0
Order By: Relevance
“…L-glutaminase with its proven abilities to use in the food industry and cancer treatment has become more important in the last few decades 35 . The other L-glutaminase applications are in culture medium as glutamine biosensor 6,7 , in GABA 8 and theanine synthesis 9 and also to measure the reaction rate of threonine synthesis 10 . L-glutaminase by releasing L-glutamate as a flavor enhancer amino acid from L-glutamine can be used in the food industry 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…L-glutaminase with its proven abilities to use in the food industry and cancer treatment has become more important in the last few decades 35 . The other L-glutaminase applications are in culture medium as glutamine biosensor 6,7 , in GABA 8 and theanine synthesis 9 and also to measure the reaction rate of threonine synthesis 10 . L-glutaminase by releasing L-glutamate as a flavor enhancer amino acid from L-glutamine can be used in the food industry 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of sucrose and yeast extract as carbon and nitrogen source improved Lglutaminase production by Zygosaccharomyces rouxii while higher L-glutaminase production was noticed in Providencia species with glucose and urea as carbon and nitrogen source, respectively. Recently, there are several reports which confirm the fact that the carbon and nitrogen sources significantly affect the production of Lglutaminase by microorganisms (Sathish and Prakasham, 2013;Krishnakumar et al, 2011;Pandian et al, 2014;Jesuraj et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…RSM was used for optimization and the bacterium grown in the optimized medium [arabinose (2%), skim milk (4%) and sodium chloride (2%)] yielded L-glutaminase activity of 1.34 IU/mg. Jesuraj et al (2017) has reported statistical optimization of L-glutaminase production by mutated strain Aeromonas veronii by PBD and CCD. The model was found to be a perfect fit in terms of maximizing enzyme yield, with the productivity improving at every stage to a fourfold output of enzyme (591.11 ±7.97 IU/mL) compared to the native strain (135±3.51 IU/mL).…”
Section: Optimization Using Ccdmentioning
confidence: 99%
“…Also, Vibrio azureus JK-79 also was good producer of glutaminase [7]. Aeromonas veronii has been identified as potential producer of lglutaminase [8].…”
Section: Introductionmentioning
confidence: 99%